Retirement and cognitive aging in a racially diverse sample of older Americans - Andel, Ross; Veal, Britney M; Howard, Virginia J; MacDonald, Leslie A; Judd, Suzanne E; Crowe, Michael (Journal of the American Geriatrics Society, 2023)
BACKGROUND: Retirement represents a crucial transitional period for many adults with possible consequences for cognitive aging. We examined trajectories of cognitive change before and after retirement in Black and White adults. METHODS: Longitudinal examination of up to 10 years (mean = 7.1 ± 2.2 years) using data from the REasons for Geographic and Racial Differences in Stroke (REGARDS) study-a national, longitudinal study of Black and White adults ≥45 years of age. Data were from 2226 members of the REGARDS study who retired around the time when an occupational ancillary survey was administered. Cognitive function was an average of z-scores for tests of verbal fluency, memory, and global function. RESULTS: Cognitive functioning was stable before retirement (Estimate = 0.05, p = 0.322), followed by a significant decline after retirement (Estimate = -0.15, p < 0.001). The decline was particularly pronounced in White (Estimate = -0.19, p < 0.001) compared with Black (Estimate = -0.07, p = 0.077) participants, twice as large in men (Estimate = -0.20, p < 0.001) compared with women (Estimate = -0.11, p < 0.001), highest among White men (Estimate = -0.22, p < 0.001) and lowest in Black women (Estimate = -0.04, p = 0.457). Greater post-retirement cognitive decline was also observed among participants who attended college (Estimate = -0.14, p = 0.016). While greater work complexity (Estimate = 0.92, p < 0.05) and higher income (Estimate = 1.03, p < 0.05) were related to better cognitive function at retirement, neither was significantly related to cognitive change after retirement. CONCLUSION: Cognitive functioning may decline at an accelerated rate immediately post-retirement, more so in White adults and men than Black adults and women. Lifelong structural inequalities including occupational segregation and other social determinants of cognitive health may obscure the role of retirement in cognitive aging.
Keywords: Humans; důchod; Cognition; lidé; kognitivní stárnutí; longitudinální studie; Longitudinal Studies; Aging; stárnutí; Female; Male; Cognitive Aging; kognice; senioři; Aged; kognitivní dysfunkce; Cognitive Dysfunction; ženské pohlaví; mužské pohlaví; Retirement